CONTRACTUAL RELATIONS IN A DAGESTANI AUL: THE JOURNAL OF THE UNCHUKATL RURAL COURT (1898–1900) - Alibekov, Hizri Gadzievic; Abdulmazidov, Ramazan Sultanovic; Anikeeva, Tat'ana Aleksandrovna (History, Archeology and Ethnography of the Caucasus, 2025)
This study focuses on the source and textual analysis of a unique historical document—the journal (daftar) of the village court of Unchukatl, Kazikumukh District, Dagestan, for the period from November 1898 to May 1900. This manuscript, covering fifteen months of life in a Dagestani village at the turn of the 20th century, is an invaluable source for studying legal, economic, and social relations in a rural community under the influence of the Russian Empire while simultaneously preserving elements of traditional ways of life. Given the lack of direct written sources reflecting the daily life of a Dagestani village during this period, this journal provides exceptional evidence for reconstructing the mechanisms of local legal proceedings, identifying the main types of business transactions, analyzing the involvement of various segments of the population, including women, in economic activity, and determining the specifics of debt obligations, purchase and sale, rental, and family relations. The purpose of this work is a comprehensive analysis of the structure and content of the Unchukatl village court journal, including a source study of the manuscript, a textual examination of key documents, a statistical analysis of the thematic distribution of transactions, and a critical assessment of the socioeconomic processes reflected in these records. Particular attention is paid to identifying the specifics of legal practice, the interaction of traditional norms and external influences, and the role of women in legal relations. The presented data, along with detailed tables and their interpretation, are intended to expand our understanding of the history of Dagestan and the specific functioning of rural communities on the periphery of the Russian Empire in the late 19th century.
Keywords: Dagestan; rural court; daftar; legal culture; adat; sharia; socio-economic relations; debt obligations; book culture